The Great Democracies, 1958 - Churchill, Winston S. (History of the English-Speaking Peoples., 2013)
The final volume of the Prime Minister's four-part history of Britain brings the nation from the Napoleonic Wars to the Boer War of 1902. In the "wilderness" years after Sir Winston Churchill unflinchingly guided his country through World War II, he turned his masterful hand to an exhaustive history of the country he loved above all else. And the world discovered that this brilliant military strategist was an equally brilliant storyteller. In 1953, the great man was awarded the Nobel Prize for Literature for "his mastery of historical and biographical description as well as for brilliant oratory in defending exalted human values." This final volume in Churchill's extraordinary, sweeping history follows Britain from the conclusion of the Napoleonic Wars to the Boer War of 1902. In it, Churchill makes an impassioned argument for the crucial role played by the English-speaking people in exporting not just economic benefits, but political freedom by encouraging democracy throughout the world. Churchill's passion for this era-informed by his own experience as a soldier and a wartime journalist during the Boer War-shines through in this thrilling conclusion to his historic work. "This history will endure; not only because Sir Winston has written it, but also because of its own inherent virtues-its narrative power, its fine judgment of war and politics, of soldiers and statesmen, and even more because it reflects a tradition of what Englishmen in the hey-day of their empire thought and felt about their country's past."--The Daily Telegraph.